Comparison of Rapid Typhidot Test Based on Sanitation Environment in Healthy Individuals in Medan - Robby Awaluddin Perangin-Angin; Rina Amelia; Jelita Siregar (TALENTA Publisher, Universitas Sumatera Utara, 2024)
Typhoid fever is a gastrointestinal tract infectious disease frequently found endemic in Indonesia, which can be transmitted by oro-fecal from food or water contaminated directly or vector carries these bacteria. Medan Belawan subdistrict has a high rate of diarrhea cases and a low percentage of a health-house model. Otherwise, the Medan Petisah subdistrict has fewer diarrhea cases and a high percentage of the health-house model. This study was aimed to compare the presence of antibodies from the Typhidot Test in people living in poor and healthy sanitation conditions. This study is an observational study with a cross-sectional design. The population is all people around Medan Petisah and Medan Belawan health center. All data were calculated using SPSS and analyzed with Chi-Square and Regression Logistics tests. The result indicates no significant association between the presence of IgM and IgG from the results of the Typhidot test on environmental sanitation in Medan (p>0.05). Thus, it can be concluded that Sanitation conditions did not affect the formation of IgM and IgG against Salmonella Typhi bacteria.